PENERAPAN SISTEM MANAJEMEN MUTU ISO 9001:2008 DALAM PENYELENGGARAAN PENDIDIKAN DI PROGRAM STUDI KEAHLIAN TEKNIK BANGUNAN SMK NEGERI 5 BANDUNG - Nurlailah, - (2014)
Quality Management System ISO (International Standards Organization) 9001: 2008 is a system used to set the policy or an official statement by top management related to the care and direction of the organization in the field of quality. Vocational High School Bandung 5 certified by the International Standards Organization 9001: 2008. Then, researchers conducted a study on the application of the Quality Management System International Standards Organization 9001: 2008 in education, especially in the workshop and Building Engineering and Stone ConcreteConstruction Engineering Vocational High School 5 Bandung. In the implementation of the Management System of Quality International Standards Organization 9001: 2008 are still complaints from students and teachers at the workshop in terms of facilities and infrastructure. The purpose of this research among which determine the application of Quality Management System International Standards Organization 9001: 2008 in the establishment of workshops on management skills Stone Concrete Construction Engineering and Building Engineering Vocational High School 5 Bandung. And to know the students in the learning at workshop discipline which has implemented the International Standards Organization 9001: 2008. This research used a descriptive-quantitative method. The variable in thisresearch is a single variable. Source of data obtained by researchers that informant data sources, documents, and observations. The sample of this research using a sample of 99 random with a sample of respondents to the questionnaire, and to interview 4 respondents. Technique data collecting questionnaires, interviews, and documentation. In this research the validity of the data by using the Pearson product moment formula. Based on the analysis and discussion in this research it can be concluded that the Vocational High School 5 Bandung has implemented a Quality Management System International Standards Organization 9001: 2008, especially in the workshop Building Engineering and StoneConcreteConstruction Engineering. So by implementing a Quality Management System International Standards Organization 9001: 2008 on school students have carried out the order or has run discipline. Keywords: Implementation, Quality Management System ISO (International Standards Organization) 9001: 2008, Discipline, Workshop. Sistem Manajemen Mutu ISO (International Standard Organization) 9001:2008 adalah sistem yang digunakan untuk menetapkan kebijakan (policy) atau pernyataan resmi oleh manajemen puncak berkaitan dengan perhatian dan arah organisasinya dibidang mutu. Sekolah Menengah Kejuruan Negeri 5 Bandung yang telah mendapatkan sertifikat International Standard Organization 9001 : 2008. Maka, peneliti melakukan penelitian mengenai penerapan Sistem Manajemen Mutu International Standard Organization 9001:2008 dalam penyelenggaraan pendidikan terutama pada workshop Teknik Gambar Bangunan dan Teknik Konstruksi Batu Beton di Sekolah Menengah Kejuruan Negeri 5 Bandung. Dalam implementasi Sistem Manjemen Mutu International Standard Organization 9001:2008 masih adanya keluhan dari siswa-siswi dan guru di workshop dari segi sarana dan prasarana. Tujuan penelitian ini diantarnya mengetahui penerapan Sistem Manajemen Mutu International Standard Organization 9001:2008 dalam penetapan manajemen penyelenggaraan workshop pada keahlian Teknik Konstruksi Batu Beton dan Teknik Gambar Bangunan Sekolah Menengah Kejuruan Negeri 5 Bandung. Dan untuk mengetahui kedisiplinan siswa pada pembelajaran diworkshop yang telah menerapkan International Standard Organization 9001:2008. Penelitian ini menggunakan metode deskriptif-kuantitatif. Variabel dalam penelitian ini adalah variabel tunggal. Sumber data yang diperoleh peneliti yaitu sumber data informan, dokumen, dan observasi. Sampel penelitian ini menggunakan sampel Randomm dengan jumlah sampel 99 responden untuk angket, dan untuk wawancara 4 responden. Teknik pengumpulan data yang dilakukan adalah angket, wawancara, dan dokumentasi. Dalam penelitian ini validitas data dengan menggunakan rumus pearson product moment . Berdasarkan hasil analisis dan pembahasan dalam penelitian ini dapat disimpulkan bahwa Sekolah Menengah Kejuruan Negeri 5 Bandung sudah mengimplementasikan Sistem Manajemen Mutu International Standard Organization 9001:2008 khususnya dalam workshop Teknik Gambar Bangunan dan Teknik Konstruksi Batu Beton. Maka dengan mengimplementasikan Sistem Manajemen Mutu International Standard Organization 9001:2008 pada sekolah siswa telah melaksanakan tata tertib atau telah menjalankan kedisiplinan. Kata Kunci: Penerapan , Sistem Manajem Mutu ISO (International Standard Organization) 9001:2008 , Kedisiplinan, Workshop.